Implementasi paradigma integrasi-interkoneksi dalam studi manajemen sumber daya manusia - Achmad Muhammad; Ruspita Rani Pertiwi (Tajdidukasi: Jurnal Penelitian dan Kajian Pendidikan Islam, 2019)
This research conducted in August-September 2005 under supervision by Lembaga Penelitian UIN Sunan Kalijaga. The main objective was to accelerate the transformation of IAIN to UIN Sunan Kalijaga in the management area. Why management? Because although successful universities are successful primarily because of their teaching and research not because of their management, good management can over time provide the conditions in which teaching and research can flourish, just as, more usually, poor management can undermine teaching and research and precipitate institutional decline. Lecturer as the main actor of teaching and research in universities has a unique characteristic compared to any kind of human resources. Its job descriptions range from serve college student by teaching, serve the scientific world by writing and research, serve institutions by administrative work, to another kind of job descriptions as a social worker who has to serve and develop the community. With those kinds of characteristics, the university has to design special human resource management, we called it Talent Management. A combination of the direct and indirect interview was used to collect primary data. Populations for this research were university and faculty leader or manager who have the authority to design policy about the lecturer. Samples were taken by using proportional consideration: university management consists of the rector and deputy rector II and faculty management consist of the dean of Dakwah, Syari'ah, and Adab and four chiefs of the study program. This research also conducted observations in daily lecturer management practices. Secondary data were compiled from the university’s document, homepages, and faculty’s document.